Traffic Accident Cost Analysis Using The Gross Output (Human Capital) Method Approach - Yogi Oktopianto; Widi Yau Hastuti; Riza Phahlevi Marwanto (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2024)
Based on the Tangerang Police traffic accident data, there were 1,559 accidents that occurred in Tangerang Regency during the last 5 years and have increased every year. These problems need to be studied to determine the factors that cause accidents from the characteristics, and the amount of accident costs as an effort to improve traffic safety on the highway. The study used the EAN (Equivalent Accident Number) method to calculate accident rates and The Gross Output method to calculate accident costs. Based on the calculation of The Gross Output method, the total unit cost of accident victims is Rp. 2,084,725,349.34, - and the amount of accident victim costs is Rp. 9,817,644,067.75, -. The unit cost of an accident is Rp. 2,127,225,346.43, - and the amount of accident costs is Rp. 10,041,644,067.75.